Mycobacterium tuberculosis diagnosed promptly by bronchial brushing cytology in an immunocompetent patient. Issue 4 (10th December 2019) - Suo, Liye; Sheu, Tiffany G.; Crumley, Suzanne M.
Abstract: Respiratory cytology plays an important role in the diagnosis of lower respiratory tract infection. The timely diagnosis of pulmonary tuberculosis (TB) can be very challenging due to the nonspecific cytomorphologic features and limited number of organisms, especially in the immunocompetent patients. Here, we reported a case of TB diagnosed promptly by bronchial brushing cytology in a 51‐year‐old immunocompetent patient. She presented with a 4 cm fungating lesion involving right lower lobe of the lung and mediastinal lymphadenopathy with an initial concern for malignancy. Bronchial brushing showed scattered acute inflammatory cells in the background of necrosis. A cell block was prepared and acid‐fast bacilli (AFB)‐positive organisms were identified. Subsequent polymerase chain reaction (PCR) performed on the sputum detected Mycobacterium tuberculosis . This case highlights the importance of recognizing the cytomorphology of TB from a bronchial brushing specimen; and also emphasizes the potential utility of the cell block from respiratory cytology in the diagnosis of TB.